An Experience with Repair of Incisional Hernias - Khan, Abdul Samad; Khan, Taj Muhammad; Rahim, Rehana (Journal of Postgraduate Medical Institute, 2011)
A review study of 78 cases of incisional hernia repair is presented, performed over a period of four years, i-e. December 1986 to December 1990. Repair of incisional hernia accounted for 5.2% of repairs of all herniae. Various factors causing this iatrogenic hernia are identified, leading being pulmonary disease before surgery and in the immediate postoperative period and wound contamination.